Karakterisasi dan identifikasi bakteri asam laktat proteolitik asal ikan depik (Rasbora tawarensis) fermentasi - Faidha Rahmi; Fita Ridhana; Murna Muzaifa (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Belacan depik is one of the fermented products made from depik fish (Rasbora tawarensis). Fermented fish products often involve lactic acid bacteria (LAB) in the production process, but scientific studies on indigenous microorganisms, including LAB, have not been reported. This study aims to characterize and identify LAB originating from depik belacan, especially those with proteolytic activity. This research is exploratory laboratory research, consisting of making depik belacan, isolation and characterization of LAB, proteolytic LAB screening, and molecular identification of LAB. Three pure isolates suspected of LAB were obtained with different colonies, namely B1, B2, and B3. The three isolates had varied morphological and biochemical characteristics. Only two isolates were confirmed as LAB with positive and negative catalase and Gram test results. Of the two LAB isolates, only isolate (B1) was able to break down protein, so this isolate was a potential starter in the depik fish fermentation. Isolate B1 was identified molecularly as Enterococcus faecium strain DT-2 with a homology of 98.18% and Query Cover 100%. This isolate needs to be further confirmed for its ability as a potential starter in improving the quality of fermented depik fish.